2018
DOI: 10.2147/opth.s163451
|View full text |Cite
|
Sign up to set email alerts
|

Somatotype, the risk of hydroxychloroquine retinopathy, and safe daily dosing guidelines

Abstract: PurposeThe aim of this study was to determine whether somatotype influences the risk of hydroxychloroquine (HC) retinopathy (HCR) and whether dosing by real body weight (RBW), ideal body weight (IBW), or the lesser of these better predicts the risk of HCR.Patients and methodsA total of 565 patients taking HC for whom height and weight were recorded and a sensitive ancillary testing modality was used including 10-2 visual fields, spectral domain optical coherence tomography, fundus autofluorescence imaging, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 11 publications
0
19
0
7
Order By: Relevance
“…The incidence of retinopathy differs based on year and screening modality used. Compared with early estimates suggesting low risk with standard drug doses [90], studies using modern screening techniques report retinopathy prevalence of up to 8% [91,92]; however, limitations exist to this literature base [89]. The risk of retinopathy is higher with increasing age, dose, and duration of usage [91,[93][94][95].…”
Section: Retinopathymentioning
confidence: 99%
“…The incidence of retinopathy differs based on year and screening modality used. Compared with early estimates suggesting low risk with standard drug doses [90], studies using modern screening techniques report retinopathy prevalence of up to 8% [91,92]; however, limitations exist to this literature base [89]. The risk of retinopathy is higher with increasing age, dose, and duration of usage [91,[93][94][95].…”
Section: Retinopathymentioning
confidence: 99%
“…In recent representative studies, the prevalence of HCQ retinopathy has been reported to range from 4.3% to 13.8% (4)(5)(6)(7)(8). These studies cannot be directly compared, because they vary in many important aspects, including the number of participants who have taken HCQ for 10 years or longer.…”
Section: Dosingmentioning
confidence: 99%
“…However, it affects 3.1% of patients treated for more than 20 years. The prevalence of retinal toxicity assessed by more modern and sensitive methods such as spectral-domain optical coherence tomography (SD-OCT) and 10-2 visual field analyser (VFA)is much higher, estimated at 7.5% [24 , 25] . More precisely, this toxicity is estimated at less than 2% within the first 10 years of use but at almost 20% after 20 years of use [24] .…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, this toxicity is estimated at less than 2% within the first 10 years of use but at almost 20% after 20 years of use [24] . The daily dose of 4-AQ plays a major role since patients treated with more than 5 mg/kg/day have 5–7 times more toxicity [24 , 25] .…”
Section: Introductionmentioning
confidence: 99%